SCIROCCO: Health System Conditions for Scaling Integrated Care in Latin American Contexts - Gómez Duarte, Ingrid (2025)
The presentation analyzes how to adapt the SCIROCCO model to assess the maturity of Latin American health systems in relation to integrated care, considering their fragmented structures and diverse sociocultural and plurinational contexts. It offers a critical reading of the original European framework, emphasizing the need for territorial contextualization, local diagnostics, and person-centered approaches. Key conditions for scaling up integrated care include institutional readiness, political coordination, regional cooperation, and the development of interdisciplinary teams, with implementation planned for 2025–2026. The approach is grounded in adaptive social complexity and capacity-building rooted in Latin American realities.